II All-Ukrainian Scientific Conference " Theoretical and applied aspects of Biography (to the 160th anniversary of the birth of D. I. Bagaliy)" (Kharkiv, November 7, 2017) - Чугуй, Тарас; Вовк, Ольга (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
II All-Ukrainian Scientific Conference " Theoretical and applied aspects of Biography (to the 160th anniversary of the birth of D. I. Bagaliy)" (Kharkiv, November 7, 2017)